PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SDN 019 SEKELADI - Suriana, Suriana; Noviana, Edddy; Alpusari, Mahmud (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The problem this research does because the students achievement of social studies fourth graderes students at SDN 019 Sekeladi still low with an average value 57.60 and Minimum completeness criteria ( KKM ) social studies is 65. Between students, which amounting to 23 students only 6 students completeness. Formulation of the problem